(untitled) (Journal of Shaheed Suhrawardy Medical College, 2026)
Context: Acute confusional state (ACS) which is a frequent medical emergency among hospitalized patients is often associated with different factors, resulting from different etiologies. Electrolytic imbalance especially disturbance in sodium serum level, is considered one of the manageable factors in the management of ACS. Methodology: This cross-sectional observational study was conducted in the Department of Medicine, Shaheed Suhrawardy Medical College Hospital, Dhaka with a duration of six months. A total of 100 patients with clinically diagnosed ACS were enrolled. Each patient underwent clinical evaluation and various laboratory investigations including serum electrolytes measurement, with their consent. Data were analyzed using SPSS; p<0.05 was considered as statistically significant Results: In this study, male patients were predominant (61%) and mean age of the patients was 6.38 years. Cerebrovascular disease was found to be the leading cause of ACS (38%), followed by pneumonia (14%) and meningitis (13%). Serum sodium disturbances were observed in 18% of cases—hyponatremia in 15% and hypernatremia in 3%—while 82% had normal sodium serum levels. Differences between sodium categories were not statistically significant (p > 0.05). Most patients (76%) recovered without sequelae; mortality was 6%. Conclusion: ACS is a common medical condition in tertiary level hospital of Bangladesh, where Hyponatremia is a common complication. Patients who develop ACS have high disability, complication rate and longer length of stay than any other patients. Knowing the nature and timing of the disease, together with the identification of high-risk patients are essential to reduce complications and improve outcome. J Shaheed Suhrawardy Med Coll 2024; 16(2): 63-68